2005
DOI: 10.1007/s10620-005-2952-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Instrument to Assess and Predict Satisfaction and Poor Tolerance Among Patients Undergoing Endoscopic Procedures

Abstract: We aimed to test the reliability of a developed questionnaire that measures and predict aversive endoscopic experience. Two questionnaires (pre- and postprocedure) were given to patients presenting for routine endoscopy. The first questionnaire elicited demographics, prior endoscopic experience, history of drug or alcohol use, patient expectations, and levels of anxiety and nervousness before procedure. After endoscopy, tolerance and willingness to repeat the examination were determined. The primary outcome of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 13 publications
3
58
0
5
Order By: Relevance
“…Previous studies have shown that there are indeed many factors that affect patient satisfaction, including patient perception of physician technical skills and sedation adequacy 13 ; facility cleanliness, privacy, and nurse attention 14 ; procedure waiting time 15 ; baseline patient anxiety 16 ; and the use of psychotropic or narcotic drugs. 17,18 The patient's age, sex, education level, and socioeconomic class are also known to influence satisfaction scores. 7,19,20 Because an adequate withdrawal phase is thought to be an essential feature of quality colonoscopy, 4 there has been interest in methods that can improve withdrawal time.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that there are indeed many factors that affect patient satisfaction, including patient perception of physician technical skills and sedation adequacy 13 ; facility cleanliness, privacy, and nurse attention 14 ; procedure waiting time 15 ; baseline patient anxiety 16 ; and the use of psychotropic or narcotic drugs. 17,18 The patient's age, sex, education level, and socioeconomic class are also known to influence satisfaction scores. 7,19,20 Because an adequate withdrawal phase is thought to be an essential feature of quality colonoscopy, 4 there has been interest in methods that can improve withdrawal time.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that (4,10,11,20,30) ; no consensus in the literature has been firmly established to date (1,22,24,26) . Longer colon, particularly the transverse, which predisposes to a more convoluted sigmoid colon, associated with acute angles due to the narrower pelvic cavity, combine to result in a more difficult procedure in women (30,32) .…”
Section: Gendermentioning
confidence: 99%
“…There is evidence that oxygen supplementation reduces the risk of hypoxemia during colonoscopy (Holm et al, 1999) but there are studies showing that when given supplemental oxygen, oxygen saturation levels do not reflect the ventilation function and may mask the CO 2 retention (Lazzaroni&Bianchi, 2001). However, a recent Australian study conducted by anesthesiologists showed that the use of supplemental oxygen was universal (Pena et al, 2005). Preparing medical personnel in the management of airway obstruction and apnea is essential.…”
Section: Positive Effects Negative Effectsmentioning
confidence: 99%